The orginal Eq. [15] included incorrect subscripts on θ. The equation was published as follows: 
\begin{eqnarray*}&&\begin{array}{ll}n{=}1&\mathrm{{\phi}}{-}\mathrm{{\theta}}_{1}{=}P_{1}\frac{N_{\mathrm{p}}^{(1)}}{b^{E}}\\n{=}2&\mathrm{{\theta}}_{2}{-}\mathrm{{\theta}}_{1}{=}P_{2}\left[\frac{N_{\mathrm{p}}^{(2)}}{b^{2E}}{+}(1{-}P_{1})\frac{N_{\mathrm{p}}^{(1)}}{b^{E}}\right]\\n{=}3&\mathrm{{\theta}}_{3}{-}\mathrm{{\theta}}_{2}{=}\\&&P_{3}\left[\frac{N_{\mathrm{p}}^{(3)}}{b^{3E}}{+}(1{-}P_{2})\frac{N_{\mathrm{p}}^{(2)}}{b^{2E}}{+}(1{-}P_{2})(1{-}P_{1})\frac{N_{\mathrm{p}}^{(1)}}{b^{E}}\right]\\{\vdots}&{\vdots}\\n{=}i&\mathrm{{\theta}}_{i}{-}\mathrm{{\theta}}_{i{-}1}{=}\\&&P_{i}\left[\frac{N_{\mathrm{p}}^{(i)}}{b^{i{\,}E}}{+}(1{-}P_{i{-}1})\frac{N_{\mathrm{p}}^{(i{-}1)}}{b^{(i{-}1)E}}{+}{\cdots}\right.\ \\&&\left.\ {+}(1{-}P_{i{-}1})(1{-}P_{i{-}2}){\ldots}(1{-}P_{1})\frac{N_{\mathrm{p}}^{(1)}}{b^{E}}\right]\end{array}\end{eqnarray*}
[15]
...
The correct equation is: 
\begin{eqnarray*}&&\begin{array}{ll}n{=}1&\mathrm{{\phi}}{-}\mathrm{{\theta}}_{1}{=}P_{1}\frac{N_{\mathrm{p}}^{(1)}}{b^{E}}\\n{=}2&\mathrm{{\theta}}_{1}{-}\mathrm{{\theta}}_{2}{=}P_{2}\left[\frac{N_{\mathrm{p}}^{(2)}}{b^{2E}}{+}(1{-}P_{1})\frac{N_{\mathrm{p}}^{(1)}}{b^{E}}\right]\\n{=}3&\mathrm{{\theta}}_{2}{-}\mathrm{{\theta}}_{3}{=}\\&&P_{3}\left[\frac{N_{\mathrm{p}}^{(3)}}{b^{3E}}{+}(1{-}P_{2})\frac{N_{\mathrm{p}}^{(2)}}{b^{2E}}{+}(1{-}P_{2})(1{-}P_{1})\frac{N_{\mathrm{p}}^{(1)}}{b^{E}}\right]\\{\vdots}&{\vdots}\\n{=}i&\mathrm{{\theta}}_{i{-}1}{-}\mathrm{{\theta}}_{i}{=}\\&&P_{i}\left[\frac{N_{\mathrm{p}}^{(i)}}{b^{iE}}{+}(1{-}P_{i{-}1})\frac{N_{\mathrm{p}}^{(i{-}1)}}{b^{(i{-}1)E}}{+}{\cdots}\right.\ \\&&\left.\ {+}(1{-}P_{i{-}1})(1{-}P_{i{-}2}){\ldots}(1{-}P_{1})\frac{N_{\mathrm{p}}^{(1)}}{b^{E}}\right]\end{array}\end{eqnarray*}
[15a]
...

First Page Preview

First page PDF preview
You do not currently have access to this article.